Transfer anxiety in critical care patients and their caregivers - Ali Timuçin Atayoğlu; Merve Bat Tonkuş; Sibel Doğan (SERNEV, 2020)
Introduction: Both admission and discharge in the critical care units can cause anxiety in the patients and their family caregivers. Coordination and integration of primary and secondary healthcare is important for those individuals. The aim of the study was to investigate the transfer anxiety in patients and their caregivers due to being transferred from the intensive care unit (ICU).Methods: This is a descriptive study that was carried out through interviewing with the patients and their caregivers who were hospitalized in the ICU and then transferred out due to the improvement of their general condition. The data of the study were carried out by using a Questionnaire Form and the State-Trait Anxiety Inventory (STAI).Results: A total of 170 individuals (85 patients and 85 family caregivers) were involved in the study. The patient's anxiety scores were higher than their caregivers and the difference was statistically significant (p lt;0.001). The patients and their caregivers' mean anxiety scale scores after the transfer were higher in comparison with the mean scores before the transfer and the difference was statistically significant (p lt;0.001). Conclusions: Patients and their caregivers experience transfer anxiety due to being transferred from the ICU. Therefore, healthcare professionals are encouraged to make the necessary adjustments to prevent transfer anxiety. In this process, the involvement of primary healthcare professionals, in particular family physicians and nurses, who know them closely is crucial.